2012
DOI: 10.2478/s11686-012-0043-4
|View full text |Cite
|
Sign up to set email alerts
|

New genetic lineages, host associations and circulation pathways of Neorickettsia endosymbionts of digeneans

Abstract: Neorickettsia is a genus of intracellular bacteria endosymbiotic in digeneans that may also invade cells of vertebrates and are known to cause diseases of wildlife and humans. Herein, we report results of screening for Neorickettsia of an extensive collection of DNA extracts from adult and larval digeneans obtained from various vertebrates and mollusks in the United States. Seven isolates of Neorickettsia were detected by PCR and sequenced targeting a 527 bp long region of 16S rRNA. Sequence comparison and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 33 publications
2
25
1
Order By: Relevance
“…As posited by Vaughan et al [4], future studies focusing on screening digenean extracts for Neorickettsia will reveal additional host associations of these bacteria and new pathways of their circulation in nature. This has already been demonstrated in a recent study by Tkach et al [3] who found 4 species level genetic lineages of Neorickettsia in 7 species of digeneans belonging to 7 different families.…”
Section: Introductionsupporting
confidence: 58%
See 4 more Smart Citations
“…As posited by Vaughan et al [4], future studies focusing on screening digenean extracts for Neorickettsia will reveal additional host associations of these bacteria and new pathways of their circulation in nature. This has already been demonstrated in a recent study by Tkach et al [3] who found 4 species level genetic lineages of Neorickettsia in 7 species of digeneans belonging to 7 different families.…”
Section: Introductionsupporting
confidence: 58%
“…Although relatively small, this genus has received significant attention in the recent years, with a rapid increase in the number of known species level lineages in this group [1], [2], [3], [4], [5]. Neorickettsia are vertically transmitted through all stages of complex digenean life cycles.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations